Reshaping health care governance using pilot projects as public policy implementation instruments - Mélanie De Winter (International Review of Public Policy)
Pilot projects are often used to test innovations; however, pilot projects, viewed as tools, are rarely addressed as an object for research. This paper, in which pilot projects are viewed as public policy instruments producing specific effects, addresses the research question: how does the use of multidisciplinary pilot projects as experimentation and implementation instruments reshape modes of public governance in the Belgian health sector in a context of transition and ongoing devolution? An ethnographic study was conducted, focusing on the specific case of the Belgian joint plan, “Integrated Care for Better Health”, which targets chronic patients and was intended to initiate a major transition from a fragmented to an integrated care system for chronic patients. The analysis concerns the specific implementation modalities designed by the authorities, which consisted of the launch of pilot projects involving professionals in the field coming from different sectors in an iterative and incremental co-creation process. This choice caused new vertical interdependences to emerge between the levels of the health care system, transforming the roles of both the authorities and hands-on professionals involved; it also denoted a transition towards a more negotiated governance, in the course of which several types of knowledge and evidence have been mobilised.